A Comparison of the Immune Profile of Commercial Broiler Strains When Raised on Marginal and High Protein Diets - Cheema, Manzoor A.; Qureshi, M.A.; Havenstein, G.B. (International Journal of Poultry Science, 2003)
A study was conducted to compare the immunocompetence of four commercial broiler strains [Ross 3F8, Ross x Cobb, Ross 308 and Cobb x Cobb (CC)] that were fed either a marginal protein diet (D1) or a high protein diet (D2) for the starter and finisher diets, respectively. Strain CC showed comparatively higher and more persistent antibody titers against sheep red blood cells (SRBC) (P < 0.0182) as well as higher macrophage phagocytic function for SRBC uptake (P = 0.0118) than the other strains. The Ross 308 strain had significantly greater cell mediated immune response, as measured by T-lymphocyte proliferation response to phytohemagglutinin-P (PHA-P), P < 0.04) and Concanavalin-A (Con-A) (P < 0.0281), as well as for the chemotaxis response to formyl-met-leu-phe (P < 0.0019) than the other strains. The diet effect was variable for monocyte-macrophage functions, but birds on the high protein diets showed higher cell-mediated response than the birds on the low protein diets when measured by Con-A and PHA-P responses. An interaction between strains and diets was seen for antibody response with the Ross 308 showing higher titers on D1 while the CC had greater antibody response when raised on D2. These results suggest that genetic differences exist between various commercial broiler chicken lines for cell mediated, humoral and innate immune responses. Furthermore, dietary protein levels appear to influence the immune response levels of broiler chickens but the response obtained varies by strain. The results of these studies imply that immunocompetence is genetically controlled, and, therefore some measures of immunocompetence could be considered as a selection criterion while selecting for performance traits.